The Holocene History of a Subalpine Birch Forest Enclave: Subfossil Evidence from Central Sweden - Kullman, Leif (Géographie physique et Quaternaire, 1994)
ABSTRACTAspects of the Holocene history of the subalpine birch (Betula pubescens Ehrh. ssp. tortuosa (Ledeb.) Nyman) forest belt in the Scandes Mountains, Sweden, were analysed by radiocarbon dating of subfossil wood remnants forming an enclave high above the present-day birch limit. The birch population thrived continuously at the site throughout the period 8700-3400 years BP, suggesting the absence of major protracted coolings and mostly higher than present temperatures. Presumably, the disappearance of birch from the study site ca. 3400 BP, reflects substantial cooling, which is corroborated by indépendant proxy data. It is inferred that during the first few millennia of the Holocene, pine (Pinus sylvestris L.) formed the uppermost forest belt and pure birch stands were restricted to small enclaves with excessive and late-melting snow. Eventually, as climate cooled, these conditions became regionally ubiquitous and birch could spread from the pockets of favourable habitat to form the present-day subalpine birch forest belt above the coniferous forest. In the original pockets too much snow accumulated and there the birch perished.